Déploiement de l’espace muséal et engagement participatif des visiteurs : l’expérience perceptive d’une statue en ronde-bosse - Mathias Blanc (Les Cahiers de l'École du Louvre)
This article reports on fieldwork conducted at the Musée du Louvre-Lens with visitors discovering a sculpture from the Louvre, the Discophorus. To study the statue’s reception, we developed a mixed methodology based on video recordings and “annotation traces in augmented reality”. The article presents the salient results of several weeks of fieldwork with and without the digital device Ikonikat 3D. It appears that our study corroborates the strong influence of the label on the way visitors look at the sculptures. But it also shows that the use of a digital device, depending on the human-machine interaction it supports, creates a space of vision and a space of action that have consequences in terms of distance and point of view on the work being viewed. Finally, we can observe different registers of meaning in the museum situation. This leads us to use a certain perspective to accompany visitor engagement with the sculptures.